Chloe wants to ride her bicycle 30.5 miles this week. She has already ridden 14 miles. If she rides for 3 more days, write and solve an equation which can be used to determine xx, the average number of miles she would have to ride each day to meet her goal.

Answer
Attempt 1 out of 2

Equation:
Answer: xx

5 answers

To find the average number of miles Chloe needs to ride each day over the next 3 days to meet her goal of 30.5 miles, we can set up the following equation.

First, we determine how many more miles she needs to ride:

Total miles she wants to ride: 30.5 miles Miles she has already ridden: 14 miles

Remaining miles to ride = Total miles - Miles ridden Remaining miles to ride = 30.5 - 14 = 16.5 miles

Now, let's denote \( x \) as the average number of miles she needs to ride each day for the next 3 days. Since she will be riding for 3 days, we can express this as:

\[ 3x = 16.5 \]

To find \( x \), we solve the equation:

\[ x = \frac{16.5}{3} \]

Perform the division:

\[ x = 5.5 \]

So, Chloe would need to ride an average of 5.5 miles per day for the next 3 days to meet her goal.

Equation: \[ 3x = 16.5 \]

Answer: \[ x = 5.5 \]

no

Let's re-evaluate the problem and break it down step-by-step.

  1. Total miles Chloe wants to ride: 30.5 miles

  2. Miles Chloe has already ridden: 14 miles

  3. Remaining miles to ride:

    \[ 30.5 \text{ miles} - 14 \text{ miles} = 16.5 \text{ miles} \]

  4. Days left to ride: 3 days

  5. Let \( x \) be the average number of miles she needs to ride each day for the next 3 days. The equation for the total miles she needs to ride in the next 3 days would be:

    \[ 3x = 16.5 \]

  6. Now, solving for \( x \):

    \[ x = \frac{16.5}{3} \]

    \[ x = 5.5 \]

So, the setup and conclusions were correct:

  • Equation: \( 3x = 16.5 \)
  • Answer: \( x = 5.5 \)

If you believe there was a misunderstanding or a specific part that is incorrect, please clarify so I can assist you further!

Please write your equation in the form a, x, plus, b, equals, c

Sure! To express the equation in the form \( a x + b = c \), we can start from our previous equation:

We had:

\[ 3x = 16.5 \]

To put it in the desired form, we can rearrange it as follows:

  1. Subtract 16.5 from both sides:

    \[ 3x - 16.5 = 0 \]

Now it is still in a similar format, but you want it in the form \( a x + b = c \). So we can interpret the equation as:

\[ 3x + (-16.5) = 0 \]

This indicates:

  • a = 3
  • b = -16.5
  • c = 0

So, the equation in the required form is:

Equation: \[ 3x - 16.5 = 0 \]

If you want it explicitly in \( a x + b = c \) format, we can interpret it as:

\[ 3x + (-16.5) = 0 \]

Let me know if you need any more help!